2018
DOI: 10.3389/fbioe.2018.00024
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Detection of Bt Sugarcane Cry1Ab and NptII DNA and Proteins in Sugarcane Processing Products Including Raw Sugar

Abstract: Brazil is the largest sugarcane producer and the main sugar exporter in the world. The industrial processes applied by Brazilian mills are very efficient in producing highly purified sugar and ethanol. Literature presents evidence of lack of DNA/protein in these products, regardless of the nature of sugarcane used as raw material. Recently CTNBio, the Brazilian biosafety authority, has approved the first biotechnology-derived sugarcane variety for cultivation, event CTC175-A, which expresses the Cry1Ab protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
(20 reference statements)
2
11
0
Order By: Relevance
“…The research presented in this study adds to previous studies. [7][8][9]13,14,15] by using very sensitive methods for the possible detection of both the GM event-specific DNA and newly-expressed insecticidal and marker proteins. In the case of proteins, testing was done using methods that were at least 100 times more sensitive than those previously used and reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The research presented in this study adds to previous studies. [7][8][9]13,14,15] by using very sensitive methods for the possible detection of both the GM event-specific DNA and newly-expressed insecticidal and marker proteins. In the case of proteins, testing was done using methods that were at least 100 times more sensitive than those previously used and reported.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Given the importance of Brazilian sugar exports, new studies aimed to detect GM DNA or protein in raw sugar using even more sensitive methods were conducted to expand on previous studies. 7,8 The studies were done on 12 independent batches of sugar produced from three GM Figure 1. Representation of the processing of sugarcane by the Brazilian Sucro-Energy Sector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limits of detection of the methods used were low and were estimated to be 1 ng/g and 1 µg/g of refined sugar for DNA and protein, respectively. Similarly, Cheavegatti-Gianotto et al 23 who examined the loss of DNA and protein of the highly prevalent protein Rubisco, showed that sugarcane processing removed Rubisco DNA and protein to levels that were below the limit of detection of highly sensitive methods. In other words, the processing and refining of sugarcane produces a highly purified food ingredient.…”
Section: Dna and Protein Detection In Ctc91087-6 Raw Sugar Fractionsmentioning
confidence: 99%
“…These GM approvals are being tested in the field for insect resistance, glyphosate tolerance, biomass yield increase, and tolerance to abiotic stresses such as water deficit (information obtained from the company AgroBio Brasil). The first Brazilian GM sugarcane cultivars ("CTC 20 Bt, " "CTC 9001 Bt, " and "CTC 93309-4 Bt, " from the Center of Sugarcane Technology [CTC], Piracicaba, SP, Brazil), which are resistant to the sugarcane borer (Diatraea saccharalis) have already been approved and released for commercial cultivation (Cheavegatti- Gianotto et al, 2018). A rigorous, multidisciplinary risk assessment process, aiming at the potential impact on the environment and at food safety must be followed before the commercial release of GM cultivars and their progeny occur.…”
Section: Introductionmentioning
confidence: 99%